PERALIHAN HAK GUNA BANGUNAN MENJADI HAK MILIK BERDASARKAN PERATURAN PEMERINTAH NO. 18 TAHUN 2021 TENTANG HAK PENGELOLAAN, HAK ATAS TANAH, SATUAN RUMAH SUSUN, DAN PENDAFTARAN TANAH - Elsura, Aqliyah Hafifah; Lubis, Syaddan Dintara (MIZAN, Jurnal Ilmu Hukum, 2024)
In Indonesia, the need for land is increasing day by day due to a significant increase in population. This causes the value of the land to increase. The increasing value of land can result in every community always cultivating the land. Forms of land cultivation can be done in various ways such as ways that are in accordance with the law and ways that are against the law. As an effort to protect land rights owners, land certificates are issued. According to Government Regulation Number 24 of 1997 concerning Land Registration in Article 32 paragraph (1) what is meant by a certificate is, "A valid proof of rights letter as a strong means of proof regarding the physical data and legal data contained therein, as long as the physical data and legal data are in accordance with the data in the measurement letter and the land book of the relevant rights". The purpose of this study is to determine the provisions for the transfer of building use rights to ownership and to determine the process of transferring building use rights to ownership at the National Land Agency. The research method used in this study is the normative legal method. Regarding the use of the normative legal approach method, this research was conducted through Library Research. The results of this study are how the process of transferring Building Use Rights to Ownership Rights is an important step for land owners to obtain stronger legal certainty and security.